2014
DOI: 10.1681/asn.2013050527
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-29a Promotion of Nephrin Acetylation Ameliorates Hyperglycemia-Induced Podocyte Dysfunction

Abstract: Podocyte dysfunction is a detrimental feature in diabetic nephropathy, with loss of nephrin integrity contributing to diabetic podocytopathy. MicroRNAs (miRs) reportedly modulate the hyperglycemiainduced perturbation of renal tissue homeostasis. This study investigated whether regulation of histone deacetylase (HDAC) actions and nephrin acetylation by miR-29 contributes to podocyte homeostasis and renal function in diabetic kidneys. Hyperglycemia accelerated podocyte injury and reduced nephrin, acetylated neph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
156
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(175 citation statements)
references
References 47 publications
(21 reference statements)
6
156
0
1
Order By: Relevance
“…This study suggests that miR-155 −/− induced markedly decreased expression of desmin and significantly increased levels of nephrin, acetylated nephrin, and WT-1. This result was consistent with recent report indicating the biologic action of noncoding miR signaling on nephrin acetylation in podocyte microenvironments [17].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This study suggests that miR-155 −/− induced markedly decreased expression of desmin and significantly increased levels of nephrin, acetylated nephrin, and WT-1. This result was consistent with recent report indicating the biologic action of noncoding miR signaling on nephrin acetylation in podocyte microenvironments [17].…”
Section: Discussionsupporting
confidence: 94%
“…Nephrin has been shown to act as a protein tyrosin kinase that triggers biologic reaction in maintaining podocyte function and renal filtration capacity in various renal disorders [14][15][16]. And recent paper demonstrated that diabetes led to a reduction in the nephrin level in conjunction with nephrin deacetylation [17]. This study suggests that miR-155 −/− induced markedly decreased expression of desmin and significantly increased levels of nephrin, acetylated nephrin, and WT-1.…”
Section: Discussionmentioning
confidence: 75%
“…In 2010, investigators observed that deleting a component of the histone H3 lysine 4 methyltransferase complex from podocytes resulted in progressive proteinuria (37). Since then, altered DNA methylation patterns (38) and posttranslational histone changes (38)(39)(40) in podocytes have each been shown to affect glomerular cell permselectivity. Here, we observed that either deletion of EZH2 specifically from podocytes or systemic inhibition of EZH2 activity diminished levels of the repressive H3K27me3 mark, provoked Notch pathway activation, and sensitized mice to glomerular disease.…”
Section: Podocyte H3k27me3 Is Diminished and Utx Expression Is Increamentioning
confidence: 99%
“…и соавт. [36] продемонстриро-вали, что гипергликемия нарушает экспрессию miR-29b в подоцитах, приводя к снижению экспрессии в них нефрина, в то время как гиперэкспрессия miR-29а в мо-дели СД у мышей позволяла эффективно поддерживать уровни нефрина и жизнеспособность подоцитов, сохра-нять функцию почек. Недавно Kanasaki K. и соавт.…”
Section: сахарный диабет Diabetes Mellitusunclassified